Cord blood cytokine profile detection in neonates with T1D parents -- monitoring of cellular auto-reactivity using protein microarray - Böhmová, Kristýna; Hladíková, Zuzana; Černý, Miloš; Flajšmanová, Kateřina; Libá, Zuzana; Škramlíková, Tereza; Špálová, Ivana; Černá, Marcela; Chudoba, Daniel; Piťhová, Pavlína; Štádlerová, Gabriela; Bartášková, Dagmar; et al. (Scandinavian journal of immunology, 2007)
Type 1 diabetes (T1D) is a great medical challenge and its incidence rises rapidly. T lymphocytes and their cytokine production are supposed to play a major role in T1D development. So far, there is no potent tool to recognize the early signs of cellular auto-reactivity which leads to beta-cell damage. The naive immune system of the newborn (not yet influenced by external factors) can be used as an important model for T1D pathogenesis studies. Cord blood samples of 22 healthy neonates born at term to a diabetic parent (T1DR) and 15 newborns with no family history of any autoimmune disease (controls) were collected. Determination of 23 cytokines was performed before and after the stimulation with diabetogenic autoantigens using protein microarray. We observed lower basal production of all detected cytokines in the T1DR group - granulocyte/macrophage colony-stimulating factor (GM-CSF) (P = 0.025), growth regulated protein (GRO) (P = 0.002), GRO-alpha (P = 0.027), interleukin (IL)-1-alpha (P = 0.051), IL-3 (P = 0.008), IL-7 (P = 0.027), IL-8 (P = 0.042), monocyte chemoattractant proteins (MCP)-3 (P = 0.022), monokine-induced by IFN-gamma (MIG) (P = 0.034) and regulated upon activation normal T-cell express sequence (RANTES) (P = 0.004). Exclusively lower post-stimulative levels of G-CSF (P = 0.030) and GRO-alpha (P = 0.04) were observed in controls in comparison with the basal levels. A significant post-stimulative decrease in G-CSF (P = 0.030) and MCP-2 (P = 0.009) levels was observed in controls in comparison with T1DR neonates. We also observed the interesting impact of the risky genotype on the protein microarray results. Protein microarray seems to be a useful tool to characterize a risk pattern of the immune response for T1D also in newborns.
Keywords: diabetes mellitus 1. typu; polymerázová řetězová reakce; Male; Pedigree; rodokmen; leukocyty mononukleární; cytokiny; Autoimmunity; mužské pohlaví; Protein Array Analysis; Autoantigens; autoantigeny; fetální krev; Fetal Blood; novorozenec; autoimunita; Leukocytes, Mononuclear; lidé; ženské pohlaví; Humans; Infant, Newborn; čipová analýza proteinů; Cytokines; Diabetes Mellitus, Type 1; Polymerase Chain Reaction; Female